Pengujian Hymen Intact bagi Wanita sebagai Salah Satu Alat Bukti Tindak Kriminal Pemerkosaan dalam Perspektif Fikih Jinayah: Intact Hymen Testing for Women as Evidence of the Crime of Rape from the Jinayah Fiqh Perspective - Bakry, Kasman; Munawara, Munawara; Febrianty, Febrianty (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2022)
This research aims to find out and understand the mechanism for testing intact hymen for women as a means of evidence of criminal acts, and its application to jinayah jurisprudence. This research is qualitative research with a type of library research that focuses on the study of manuscripts and texts, using conceptual, normative juridical and comparative approaches. The results of the research and discussion of this research are: first, intact hymant testing for women was carried out by a medical team experienced in their field. Of course, the testing mechanism is carried out structurally and with great care. The medical team examines the hymen by assessing the shape of the intact hymen and then measuring the diameter of the hymen hole using a cotton swab which is rubbed in a forward, backward, up and down direction and rotating for 20 seconds around the vulva/vagina. Then the cotton swab is rubbed on the slide. Next, spermatozoa were examined in the emergency room laboratory and vaginal swabs were carried out twice to show the results of the examination of the blood membranes. Second, the type of criminal act in jinayah jurisprudence is characterized by an argument stating the consequences or punishment. The punishment for this form of crime is usually called hudud. As for crimes/criminals that are not mentioned in detail in the arguments/nas, the punishment is determined by the competent judge. Third, in essence, intact hyment testing is not permitted unless it is an emergency and there is a benefit in it. What is permissible if the factors behind this aim to uncover cases of criminal acts of rape.